2021
DOI: 10.3390/molecules26216377
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Modulates the Expression of HSPA and Activates Apoptosis in Two Cell Lines of Human Colorectal Cancer

Abstract: Betulinic acid (BA) is a pentacyclic triterpene usually isolated from botanical sources. Numerous studies have reported the inhibitory effect of BA against human colorectal cancer cells (CRC). However, its effect on the expression of the molecular chaperone HSPA is unclear. The aim of this research is to investigate the anti-cancer activities of BA purified from Piper retrofractum and study its effect on the expression of HSPA in colorectal cancer HCT116 and SW480 cells. The viability of both cancer cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Betulinic acid inhibits colon cancer cell growth and metastasis by regulating the TGF-β/Smad signaling pathway. It causes Smad protein receptor phosphorylation [ 109 ]. ANP32A is highly expressed in CRC tissues, correlating with their low differentiation, and is accompanied by the over-activation of AKT and reduced phosphorylation of p38.…”
Section: Histone Phosphorylation Regulates Crcmentioning
confidence: 99%
“…Betulinic acid inhibits colon cancer cell growth and metastasis by regulating the TGF-β/Smad signaling pathway. It causes Smad protein receptor phosphorylation [ 109 ]. ANP32A is highly expressed in CRC tissues, correlating with their low differentiation, and is accompanied by the over-activation of AKT and reduced phosphorylation of p38.…”
Section: Histone Phosphorylation Regulates Crcmentioning
confidence: 99%
“…A recent study showed that betulinic acid (BA) is capable of inhibiting cancer progression in two colorectal cancer lines, HCT116 and SW480, by interfering with the levels of pro-apoptotic markers, increasing the levels of cleaved Bax and caspase-3 and caspase-9, and decreasing those of the antiapoptotic Bcl2. At the same time, this triterpene was able to modify the levels of the HSPA chaperone according to the concentrations of BA used by being able to bind to the nucleotide-binding domain of HSP70 in its ADP-binding state, indicating its high anticancer capacity [ 121 ].…”
Section: Biological Activities Of the Triterpenic Components Of The O...mentioning
confidence: 99%